The complete guide to sports nutrition - Bean, Anita (Complete guide series, 2017)
The Complete Guide to Sports Nutrition is the definitive practical handbook for anyone wanting a performance advantage. This fully updated and revised edition incorporates the latest cutting-edge research. Written by one of the country's most respected sports nutritionists, it provides the latest research and information to help you succeed.